Impaired type I and type III interferon induction and rhinovirus control in human cystic fibrosis airway epithelial cells. Issue 6 (2nd January 2012) - Vareille, Marjolaine; Kieninger, Elisabeth; Alves, Marco P; Kopf, Brigitte S; Möller, Alexander; Geiser, Thomas; Johnston, Sebastian L; Edwards, Michael R; Regamey, Nicolas
Abstract : This article has been retracted Vareille M, Kieninger E, Alves MP, et al . Impaired type I and type III interferon induction and rhinovirus control in human cystic fibrosis airway epithelial cells. Thorax 2012 Jun;67:517-25. This article has been retracted. In our article recently published in Thorax, we described a novel mechanism explaining the increased susceptibility of patients with cystic fibrosis (CF) to rhinovirus infections, namely defective interferon type I and III production by CF airway epithelial cells. In experiments performed after publication of the article we were unable to consistently replicate our findings of deficient interferon type I and III production by CF airway epithelial cells upon rhinovirus infection. In the light of these results, we carried out detailed investigations of the data reported in the above manuscript and regrettably found evidence of deliberate manipulation of experimental data by the first author Dr M. Vareille. This manipulation was accompanied in some instances by absence of original data files. The manipulation/original data absence involved data presented in most, if not all of the figures, thus we wish to fully retract the paper and apologise to the readers of Thorax and to the scientific community for the inconvenience this has caused. We also checked data published by our group in manuscripts on which Dr Vareille was a co-author and found that data published in these manuscripts had not been manipulated. These two manuscripts, whose data and conclusions we stand by are: Edwards MR, Regamey N, Vareille M, Kieninger E, Gupta A, Shoemark A, Saglani S, Sykes A, Macintyre J, Davies J, Bossley C, Bush A, Johnston SL. Impaired innate interferon induction in severe therapy resistant atopic asthmatic children. Mucosal Immunol. 2013 Jul;6:797-806. doi: 10.1038/mi.2012.118. Epub 2012 Dec 5. PMID:23212197 and Kieninger E, Vareille M, Kopf BS, Blank F, Alves MP, Gisler FM, Latzin P, Casaulta C, Geiser T, Johnston SL, Edwards MR, Regamey N. Lack of an exaggerated inflammatory response on virus infection in cystic fibrosis. Eur Respir J. 2012 Feb;39:297–304. doi: 10.1183/09031936.00054511. Epub 2011 Jun 30. PMID:21719483. Dr. Vareille has received a letter from the Secretary General of the University of Bern condemning her scientific misconduct as a severe offence against the rules of scientific integrity. Her current employers have also been informed. All co-authors of the publication including Dr. Vareille concur with the retraction statement.